2021
DOI: 10.1111/1440-1703.12258
|View full text |Cite
|
Sign up to set email alerts
|

Forest fragmentation drives liana community structure but not the patterns of liana–tree interaction network in two forest ecosystems in Ghana

Abstract: We assessed fragmentation impact on liana community structure and patterns of liana-tree interaction network structure, and edge effects on liana community structure in a rainforest and a moist semi-deciduous (MSD) forest in Ghana. In each forest, we randomly established 30 20 Â 20 m 2 plots at varied distances (0-20 m, 20-40 m, 40-60 m, 60-80 m, 80-100 m) from forest edge to interior in fragmented and intact sites. Lianas with diameter at 1.30 m from rooting base ≥1 cm and their host trees (diameter at breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 65 publications
3
5
0
Order By: Relevance
“…We found anti‐nested and modular structure in the three liana‐tree interaction networks in AFR. This trend has also been reported by Addo‐Fordjour and Afram ( 2021 ), and Addo‐Fordjour et al ( 2021 ), and to some extent by Magrach et al ( 2016 ) whose liana‐tree networks showed anti‐nested structure (see supplementary data in Magrach et al, 2016 ). Nevertheless, our results contrast with Sfair et al ( 2010 ), who recorded nested structure in three distinct vegetation formations in Brazil, and also differs from the networks of Sfair et al ( 2015 ), which did not show modularity.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…We found anti‐nested and modular structure in the three liana‐tree interaction networks in AFR. This trend has also been reported by Addo‐Fordjour and Afram ( 2021 ), and Addo‐Fordjour et al ( 2021 ), and to some extent by Magrach et al ( 2016 ) whose liana‐tree networks showed anti‐nested structure (see supplementary data in Magrach et al, 2016 ). Nevertheless, our results contrast with Sfair et al ( 2010 ), who recorded nested structure in three distinct vegetation formations in Brazil, and also differs from the networks of Sfair et al ( 2015 ), which did not show modularity.…”
Section: Discussionsupporting
confidence: 80%
“…Generally, our study adds to the number of studies that have demonstrated the existence of non‐nestedness and modularity in liana‐tree networks (e.g. Addo‐Fordjour & Afram, 2021 ; Addo‐Fordjour et al, 2021 ; Magrach et al, 2016 ).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations